A compass to guide EU policy in support of business competitiveness - Fredrik Erixon; Oscar Guinea; Philipp Lamprecht; Vanika Sharma; Elena Sisto; Erik Van der Marel (European Centre for International Political Economy (ECIPE), 2022)
The EU agenda for improving competitiveness is missing in action. Economic competitiveness has been a central plank in the development of the European Union - a relentless quest for policies that lead to more prosperity and that make European companies in world markets more successful. However, since the end of the Lisbon Agenda in 2010, economic competitiveness seems to have fallen off the EU map. This Agenda had its flaws, but it rightly sought to make Europe "the most competitive and dynamic knowledge-economy in the world". The impression now is that Europe is on the retreat and the current European Commission is the first without a strategy to strengthen competitiveness at the EU level since the early 1990s. Hopefully, a course correction may now be on its way. Ursula von der Leyen has promised a "competitiveness check" on new EU policy. With the strong economic headwinds facing Europe and the world, the EU needs to pursue structural economic reforms that raise productivity and growth. This report offers a map and a competitiveness compass for the EU to find a new path towards a flourishing society. The report takes aim at faster economic growth in Europe. Growth is not the only target for the economy but is a prerequisite to achieve many of the non-economic objectives that are important. For instance, improved rates of growth are necessary to boost living standards in Europe, and to give many more citizens economic opportunities that have been absent after a decade of strong economic turbulence. Faster growth and stronger European competitiveness are also central in an age of increasing geopolitical frictions and war. The West and its allies are economically strong and innovative. But it is equally obvious that their economic power to command the direction of the world economy has weakened, and that the only way to fight against the economic gravity that takes more business, investment and innovation to China and other emerging economies is to make our own economies more competitive. Moreover, there is no environmental sustainability without innovation. To address climate change, Europe need as much technological progress as it can muster.
Keywords: 330; Competition; Competition policy; Regulation; EU competition law; Theory; EU states; Wettbewerb; Wettbewerbspolitik; Regulierung; EU-Wettbewerbsrecht; Theorie; EU-Staaten